2019
DOI: 10.3390/w11051097
|View full text |Cite
|
Sign up to set email alerts
|

Scour Induced by Single and Twin Propeller Jets

Abstract: Single and twin ship propeller jets produce scour holes with deposition dune. The scour hole has a maximum depth at a particular length downstream within the propeller jet. Existing equations are available to predict maximum scour depth and the corresponding scour length downstream. Experiments conducted with various physical propeller models, rotational speeds, propeller-to-propeller distances and bed clearances are presented. The measurements allowed a better understanding of the mechanism of temporal scour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The clearance effect was reported in the works such as Ong et al [29]. The distance between propeller and sand bed was set same to Cui et al [30] without quay wall.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clearance effect was reported in the works such as Ong et al [29]. The distance between propeller and sand bed was set same to Cui et al [30] without quay wall.…”
Section: Methodsmentioning
confidence: 99%
“…Cui et al [30] reported that the scour structures of internal and external rotating twin propellers without considering the effect of the quay wall were different. The jets of the internal and external rotating twin propellers formed tangential downward and upward jet components, respectively, on the symmetric plane downstream of the propellers.…”
Section: Scour Patterns Between the External-rotating And Internal-rotating Systemsmentioning
confidence: 99%
“…Previous research on twin-propeller induced scour is insufficient to estimate the scour depth for twin-propeller ship. Cui et al [16] stated that most ships used the external rotating system (turning outward over the top), and therefore the experimental data of external rotating system is used to establish the empirical model for twin-propeller. The twin-propeller scour has two connected scour holes, which can be described as the combination of two single-propeller scour holes in the preliminary stage.…”
Section: Methodsmentioning
confidence: 99%
“…Local scour is a well-defined term in river engineering and is described as the removal of sediment particles from the alluvial streams. It is recognized as the main reason for the failure of hydraulic structures [5][6][7][8]. Figure 1 shows an actual picture of the failure of a vertical spur dike in the river Gaula near Haldwani, Uttrakhand in India.…”
Section: Introductionmentioning
confidence: 99%